Extended state observer based load frequency controller for three area interconnected power system - Van Van Huynh; Phong Thanh Tran; Tuan Anh Tran; Dao Huy Tuan; Van-Duc Phan (Universitas Ahmad Dahlan, 2021)
In this paper, we develop a new extended state variable observer based LFC scheme for three-area interconnected power systems. The extended state observerbased load frequency controllers are developed which utilize disturbance estimation techniques. The propose control approach assures that the fluctuating things of the load frequencies reaches to a safer range and the load frequencies can also be made at a very minimal not to have an effect on power quality and power flow in multi-area interconnected power system. The results of the simulations using MATLAB/SIMULINK done did not only address that the proposed newly control method works effectively but also change powerfully the parameter variations of the interconnected areas of the power system. Especially, it works very well to limit disturbances impact on interconnected areas in the system. Therefore, the performance of interconnected power system under different multi-conditions is simulated with the new control method to demonstrate the feasibility of the system.